MIA로 골관절염 유발된 동물모델에서 산수유(山茱萸) 30% Ethanol 추출물의 개선 효과 - 김민주; Min Ju Kim; 이진아; Jin A Lee; 신미래; Mi-rae Shin; 박해진; Hae-jin Park; 노성수; Seong-soo Roh (大韓本草學會誌, 2020)
Objectives：The objective of this study was to investigate the therapeutic effect of Corni Fructus 30% ethanol extract (CFE) on the monosodium iodoacetate (MIA)-induced osteoarthritis rats. Methods：The subjects were divided into 4 groups ; Normal group (N, n=10), MIA-induced osteoarthritis control group (Con, n=10), indomethacin 5 ㎎/㎏ treated group (INDO, n=10), CFE 200 ㎎/㎏ treated group (CFE, n=10). Blood and articulation tissues were collected after two weeks of drug administration. Oxidative stress was analyzed with reactive oxygen species (ROS), peroxynitrite (ONOO-). And the Nuclear factor erythroid-2 (Nrf2), heme oxygenase-1 (HO-1), superoxide dismutase (SOD), catalase, glutathione peroxidase-1/2 (GPx-1/2), Nuclear Factor Kappa B p65 (NF- Bp65), cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), tumor necrosis factor-alpha (TNF ), interleukin-6 (IL-6), Interleukin 1 (IL-1 ), matrix metalloproteinase-1 (MMP-1), and tissue inhibitor of metalloproteinases-1 (TIMP-1) were investigated by western blot. Results：The administration of CFE showed a significant reduction of changes in relative hind paw weight distribution. Reactive oxygen species (ROS) and peroxy nitrite (ONOO-) levels of articulation tissues were significantly decreased in CFE compared to the control group. Western blot measurements of Nrf2, HO-1, SOD, catalase, GPx-1/2 showed that the CFE group was increased compared to the Con group. And western blot measurements of NF- Bp65, COX-2, iNOS, TNF , IL-6, IL-1 showed that the CFE group was reduced compared to the Con group. Also CFE group decreased MMP-1 and increased TIMP-1. Conclusion：Based on the above results, it can be seen that osteoarthritis is improved when Corni Fructus 30% ethanol extract treated.